Association of male pattern baldness with angiographic coronary artery disease severity and collateral development - SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (BOHN STAFLEU VAN LOGHUM BV, 2015)
Objective We aimed to investigate whether there is an association between male pattern baldness and angiographic coronary artery disease (CAD) severity and collateral development, which has not been reported previously. Methods Coronary arteriograms, CAD risk factors, lipid parameters and presence and severity of baldness in 511 male patients were prospectively evaluated. Baldness was classified into five groups. Severity of CAD was evaluated with the Gensini scoring system and collateral development with Rentrop scores. Results Although subjects with a higher Gensini score had more frequent and severe baldness, they were older than the group with lower Gensini scores. Bald patients had a higher Gensini score when compared with their non-bald counterparts. In univariate analysis, age more than 60, body mass index more than 30, smoking and baldness were predictors of high Gensini scores. In multivariate analysis, only age more than 60, body mass index more than 30 and smoking were independent predictors of a high Gensini score. There were no differences in terms of presence and severity of baldness in subjects with and without adequate collateral development. Conclusions There was no relation between presence, severity and age of occurrence of male pattern baldness and Gensini and Rentrop scores, which are important measures of presence and severity of CAD.
Keywords: Baldness; Alopecia; Coronary artery disease; Atherosclerosis; Gensini; Rentrop; ISCHEMIC-HEART-DISEASE; ANDROGENETIC ALOPECIA; MYOCARDIAL-INFARCTION; EARLY-ONSET; NATIONAL SAMPLE; HAIR LOSS; MEN; POPULATION; RISK